Condições de trabalho das educadoras em turmas de pré da Rede Municipal de Curitiba - Oliveira, Thays Teixeira de (2015)
This paper presents master's search results. The object of study are the educators in municipal public network of Curitiba in preschool classes, inside the municipal early childhood education centers (CMEIs) seeking similarities and dissimilarities in the exercise of their functions. Educator is a public worker with entitlement in high school level in the teaching mode, that works exclusively with the kindergarten. The choice for educators who work in preschool classes is due to the fact that at this stage of early childhood education is more likely to occur separation between care and education, therefore, a division of labor that may involve both hierarchical, command, or shared work with variations or not in the working conditions. Among the objectives of this research, we seek initially analyze the concept of early childhood education exposed in official documents and in reference authors in relation to the site of early childhood education within the school education, as well as the separation between care and education. Another objective is to analyze the bibliographic production of the teaching work, specifically in early childhood education, based on the categories of precarization and intensification of teaching. To learn more about the working conditions of these workers, as a methodological tool, we opted for the interviews with the most experienced teachers in preschool classes, based on privileged theoretical categories.